Expanding Parapsychology Research: Learnings from a Beneficent Funder - Wahbeh, Helane (Journal of Scientific Exploration, 2022)
Parapsychology is a research field that has seen much lower funding than other areas of science. This lack of financial support is critical with limited resources for salaries, project expenses, and support staff for researchers already in the field and those would otherwise want to join the field. BIAL Foundation Chairman Luís Portela shares why he funds parapsychology and his thoughts on increasing the funding, and thus the opportunities for breakthroughs, in the field. Keywords: bias, BIAL Foundation, collaboration, edge science, funding, phenomenology